Musical games in the creative space of a child in early and preschool age - Petrušić, Daniela (Rethinking childhood II: child and space, 2026)
Music is an art that plays a significant role in the upbringing and education of children of early and preschool age. From the earliest days, music provides children with joy, happiness and play and enhances their mental, physical, emotional and social development. Quality musical experiences at an early age improve a child’s listening skills, develop thinking, creative activity, form various personality traits, help develop a child’s speech, intelligence and creativity, encourage sociability, enrich a child’s vocabulary and improve memory. Given that musical content greatly influences a child’s overall development, it is important that music is present in the educational process in a way that is understandable to the child. In order for music to be as close to the child as possible, it is often associated with play, which is the closest and most natural activity for early and preschool children, helping them to get to know their environment and learn about the world around them. The game awakens a sense of comfort and satisfaction in the child and has a positive impact on the child’s development through an unobtrusive way. Musical games are a fun and useful tool that encourages children to easily learn different content through movement. A competent educator is crucial in implementing quality music education. He motivates children to engage in various musical activities (singing, playing, listening to music, playing musical games) and encourages them within the educational group in accordance with their needs, interests and desires. This paper will present different types of musical games, the influence of music on the game, the possibility of learning non-musical content with musical games, and the influence of musical games on the overall and musical development of children of early and preschool age. Also, the importance of the role of educators in the implementation of musical content with children of early and preschool age will be presented.